Good enough for governance? Audit and marine biodiversity offsetting in Australia. Issue 120 (March 2021) - Niner, Holly J.; Randalls, Samuel
Highlights: High uncertainty of marine offsetting processes presents risks for users of marine offsets. These risks are managed by a focus on measurement and audit rather than biodiversity goals. Marine offsets do not rely on accurate quantification of biodiversity losses and gains. Auditability is good enough to meet reputational needs of organisations. A focus on auditable offsets and marine NNL prevents transparency in ecological outcomes. Abstract: Biodiversity offsetting is often presented as a way to manage competing demands of environmental protection and economic development. It is premised on the transparent demonstration of how aims of no net loss of biodiversity (NNL) or similar are met in practice. This is complicated in marine systems where ecological predictions are commonly highly uncertain, knowledge of ecological restoration is low and administrative governance is complex. Drawing on a case study of marine biodiversity offsetting in Australia, this paper shows how these uncertainties pose practical challenges for both producers and consumers of marine biodiversity offsets, needing to progress with decision-making while meeting increasing societal pressure for demonstrable NNL. These competing needs are met through the centrality of an auditable decision-making process that contributes to establishing an organisation's social licence to operate. The need for auditability drives the use of an imprecise measure of NNL through financial equivalency and the use of strategic offsetting projects. The coarse-grained interpretation of biodiversity offsetting best practice reduces the risks posed by explicit acknowledgement of biodiversity loss, offset failure or prohibitively large offset liabilities. Strategic relationship management across government, industry, academia and non-governmental organisations has raised the profile of biodiversity and its importance, but whether the auditing process has delivered on environmental protection is an open question. What is 'good enough' to meet governance standards may have become the over-riding goal. We conclude by acknowledging that the seemingly unattainable yet expected aim of NNL for marine systems prioritises auditability above discussions of 'acceptable' risk.